2021
DOI: 10.1017/s2040174421000581
|View full text |Cite
|
Sign up to set email alerts
|

Maternal childhood trauma and prenatal stressors are associated with child behavioral health

Abstract: Maternal adversity and prenatal stress confer risk for child behavioral health problems. Few studies have examined this intergenerational process across multiple dimensions of stress; fewer have explored potential protective factors. Using a large, diverse sample of mother–child dyads, we examined associations between maternal childhood trauma, prenatal stressors, and offspring socioemotional-behavioral development, while also examining potential resilience-promoting factors. The Conditions Affecting Neurocogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 102 publications
0
19
0
Order By: Relevance
“…Exposure to various forms of stressors, including economic precarity, housing insecurity, loss of a loved one, and interpersonal violence, are well-established predictors of psychiatric problems across the life span ( 1 5 ). The impact of these experiences is disproportionately borne by women—especially women in underserved communities of color ( 6 – 9 ) and with lower incomes ( 10 )—which also places their offspring at increased risk for later psychiatric problems. Indeed, the World Health Organization considers intimate partner violence against women a “major public health problem and a violation of women's human rights,” estimating that roughly one in three women are subjected to intimate partner violence during their lifetime, with up to 13% of women experiencing intimate partner violence during pregnancy (pIPV) ( 11 ).…”
Section: Intergenerational Transmission Of Effects Of Women's Stresso...mentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to various forms of stressors, including economic precarity, housing insecurity, loss of a loved one, and interpersonal violence, are well-established predictors of psychiatric problems across the life span ( 1 5 ). The impact of these experiences is disproportionately borne by women—especially women in underserved communities of color ( 6 – 9 ) and with lower incomes ( 10 )—which also places their offspring at increased risk for later psychiatric problems. Indeed, the World Health Organization considers intimate partner violence against women a “major public health problem and a violation of women's human rights,” estimating that roughly one in three women are subjected to intimate partner violence during their lifetime, with up to 13% of women experiencing intimate partner violence during pregnancy (pIPV) ( 11 ).…”
Section: Intergenerational Transmission Of Effects Of Women's Stresso...mentioning
confidence: 99%
“…Despite the fact that prenatal stressors such as pIPV and pSLE for women can co-occur, their dual contributions to child psychopathology are rarely studied—especially in communities of color ( 17 , 28 , 29 ). This is a particularly important population within which to examine such stressors given that women of color have higher prevalence rates of intimate partner violence compared to non-Hispanic White women ( 6 – 9 ).…”
Section: Intergenerational Transmission Of Effects Of Women's Stresso...mentioning
confidence: 99%
“… 12 Similar results were observed in associations with child behaviour problems. 57 ECHO-PATHWAYS analyses in the CANDLE study population also suggest a positive association between maternal vitamin D and childhood IQ, 55 links between eating fast food in the second trimester of pregnancy and childhood obesity 56 and that maternal stressors during pregnancy are associated with her child’s early life socioemotional development 61 and executive functioning, 62 with some evidence that high quality parenting may buffer these associations. 62 In one of the largest studies of pCRH and child behaviour outcomes to date, we reported that maternal exposure to traumatic events during her childhood resulted in higher pCRH levels and rise during pregnancy.…”
Section: Introductionmentioning
confidence: 98%
“…Exposure to ACEs, along with their health and mental health consequences, may put women at increased risk for health difficulties in pregnancy (Kern et al, 2022;Mersky & Lee, 2019), as well as disrupted postpartum mental health (Racine et al, 2020). A growing body of literature demonstrates that the impact of ACEs can also be transmitted across generations, whereby maternal exposure to childhood adversity puts her infant at-risk for poor developmental health (Ahmad et al, 2021;Cooke et al, 2021;Madigan et al, 2017;Racine et al, 2018). Thus, pregnancy and the postpartum period are critical periods for targeted intervention in order to mitigate the transmission of ACEs and promote resilience (Seng, 2015).…”
Section: Introductionmentioning
confidence: 99%